2020
DOI: 10.1038/s41467-019-14152-8
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic specifications of host chromosome docking sites for latent Epstein-Barr virus

Abstract: Epstein-Barr virus (EBV) genomes persist in latently infected cells as extrachromosomal episomes that attach to host chromosomes through the tethering functions of EBNA1, a viral encoded sequence-specific DNA binding protein. Here we employ circular chromosome conformation capture (4C) analysis to identify genome-wide associations between EBV episomes and host chromosomes. We find that EBV episomes in Burkitt's lymphoma cells preferentially associate with cellular genomic sites containing EBNA1 binding sites e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 69 publications
2
87
0
1
Order By: Relevance
“…For the visualization in Fig. 6 , supplementary Fig S6 , to get a more accurate view of the contacts, we also normalized the bias caused by restriction sites with 4C-ker 25 and the significant interaction was called like Kim et al 26 ; briefly, we called the significant interaction with bdgpeakcall subcommand form MACS2 27 (-c 20 -g 3000) and the consistent peak in #1 and #2 were used. The coloration analysis of histone markers and 3C-HTGTS data was performed by multiBigwigSummary 23 (BED-file) for each chromosome separately.…”
Section: Methodsmentioning
confidence: 99%
“…For the visualization in Fig. 6 , supplementary Fig S6 , to get a more accurate view of the contacts, we also normalized the bias caused by restriction sites with 4C-ker 25 and the significant interaction was called like Kim et al 26 ; briefly, we called the significant interaction with bdgpeakcall subcommand form MACS2 27 (-c 20 -g 3000) and the consistent peak in #1 and #2 were used. The coloration analysis of histone markers and 3C-HTGTS data was performed by multiBigwigSummary 23 (BED-file) for each chromosome separately.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies using Hi-C methods examined EBV interactions with host chromosome in various cell types [40,52]. Another related study used capture Hi-C to analyze KSHV looping DNA interactions during latency and reactivation, and found that DNA loops organized around highly active RNA polymerase II promoters, especially that for the viral PAN non-coding RNA [53].…”
Section: Discussionmentioning
confidence: 99%
“…4C-seq trans interactions were determined using a "window" method as described by Kim et al, (2020). Briefly, the virus viewpoint regions at the beginning of the reads were trimmed off using Cutadapt (Martin, 2011) software and the remaining human portions were aligned to the human UCSC hg38 reference genome using bowtie2 (version 2.3.5) (Langmead et al, 2009;Langmead and Salzberg, 2012).…”
Section: C-seq Analysismentioning
confidence: 99%